2014
DOI: 10.1017/s0025100314000267
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting Mandarin ‘apical vowels’: An articulatory and acoustic study

Abstract: The present study investigates the articulatory and acoustic properties of the unique apical segments in Mandarin Chinese that occur after dental and retroflex sibilants instead of the high front vowel [i]. An ultrasound study showed that the segments are homorganic with the preceding dental and retroflex sibilants. However, an acoustic study showed that they have a periodic waveform and clear formant structures with no inherent frication noise, indicating that they are not ‘voiced fricatives’. The results als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
50
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(54 citation statements)
references
References 23 publications
4
50
0
Order By: Relevance
“…2 The acoustic analysis in Lee-Kim (2014b) showed that, in producing Mandarin [sɹ̩ ], [ɕi], and [ȿɻ ̩ ], the tongue positions do not change significantly after the tongue reaches the consonantal targets, which confirms that the consonantal and the vocalic gestures are homorganic. That is, the apical vowels are the 'vocalized prolongation' of their preceding consonants (Chao, 1934, p. 374 (Zee & Lee, 2001;Lee & Li, 2003;Cheung, 2004;Zee & Lee 2004) …”
Section: Mandarin Sibilants and Apical Vowelsmentioning
confidence: 99%
See 2 more Smart Citations
“…2 The acoustic analysis in Lee-Kim (2014b) showed that, in producing Mandarin [sɹ̩ ], [ɕi], and [ȿɻ ̩ ], the tongue positions do not change significantly after the tongue reaches the consonantal targets, which confirms that the consonantal and the vocalic gestures are homorganic. That is, the apical vowels are the 'vocalized prolongation' of their preceding consonants (Chao, 1934, p. 374 (Zee & Lee, 2001;Lee & Li, 2003;Cheung, 2004;Zee & Lee 2004) …”
Section: Mandarin Sibilants and Apical Vowelsmentioning
confidence: 99%
“…18,page 3 of 27 In Mandarin, the vowel [i] follows the palatal sibilants and most other consonants but not the dental and retroflex sibilants. As shown in (2), the dental and retroflex sibilants are followed by the homorganic syllabic approximants [ɹ̩ ] and [ɻ ̩ ] (Lee & Zee, 2003, Lee-Kim, 2014b, which are often referred to as the 'apical vowels. '…”
Section: Mandarin Sibilants and Apical Vowelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Third, frication lasts for the entire duration of the vowel, which is not the case in e.g. Standard Chinese [9]. We will also show that the three different processes are in different developmental stages.…”
Section: Consonant-vowel Coarticulationmentioning
confidence: 63%
“…They used Chinese phonetic symbols [ɿ] and [ʅ] for the Mandarin high front apical vowel and high back apical vowel. The present study substituted [ɿ] and [ʅ] with the IPA equivalents [ɹ̪ ] and [ɻ] proposed byLee-Kim (2014). available at https://www.cambridge.org/core/terms.…”
mentioning
confidence: 99%